Impact of Citrus aurantium Juice Consumption on Gestational Hypertension in Pregnant Women - Resmi Ayu Wandira; Richta Puspita Haryanti; Ida Subardiah P (Genius Journal, 2026)
Objective: The Maternal Perinatal Death Rate (MMR) in Indonesia in 2023 is 4,129, based on data from the Maternal Perinatal Death Notification (MPDN). The objective was to determine the effect of consumption of sweet orange juice (Citrus aurantium) on the reduction of blood pressure (gestational hypertension) in pregnancy in the Working Area of the Campang Raya Health Center, Bandar Lampung in 2024. Method: Research on the type of quantitative research. The research was conducted from January to February 2025 for 1 week in the working area of the Campang Raya Health Center in Bandar Lampung. Pre-Experimental design with pretest posttest with one group design Total population of 34 pregnant women with gestational hypertension, sample of 31 respondents. Puposive sample technique. Result: The average blood pressure before consumption of sweet orange juice (Citrus aurantium) was 146.13, SD 3.085. Meanwhile, diastolic blood pressure means 103.71, SD 8.848. The average blood pressure after 121.61, SD 7.460. Diastolic blood pressure means 89.52, SD 6.995. The t-test obtained a p value of 0.000< α (0.05) meaning that Ha was accepted, which means that there is an effect of consumption of sweet orange juice (Citrus aurantium) on the reduction of blood pressure (gestational hypertension) in pregnancy in the Working Area of the Campang Raya Health Center Bandar Lampung in 2024. Conclusion: By conducting this study, it can help pregnant women with gestational hypertension problems by consuming sweet oranges regularly can help lower blood pressure in pregnant women and reduce the risk of complications.